The Effect Of Psychoeducation Using A Tuberkulosis Card On The Anxiety Levels Of Tuberculosis Patients In The Orking Area Of Sikumana Public Health Center, Kupang City - Juanita Tereiza Caeiro; Febtian Chandradevi Nugroho; Fransiskus Salesius Onggang; Kinanthi Lebda Wicaksaputri (Journal of Tropical Diseases and Health Science, 2025)
Tuberculosis (TB) remains a serious health problem in Indonesia, including in Kupang City, which has the highest number of cases in NTT. TB patients not only face physical problems, but also often experience anxiety due to stigma, physical changes, and the burden of long-term treatment. Psychoeducation using TB Cards is expected to be a practical solution to help reduce patient anxiety levels. Objective: To analyze the effect of psychoeducation using TB Cards on the anxiety levels of tuberculosis patients in the working area of the Sikumana Community Health Center in Kupang City. Methods: This study used a quasi- experimental design with a one-group pre-test post-test approach. The sampling technique was accidental sampling with a total of 30 TB patients as respondents. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HARS) questionnaire. Data were analyzed using the Wilcoxon test. Results: The Wilcoxon test results showed a significant effect between psychoeducation using TB Cards and a decrease in anxiety levels among tuberculosis patients (p-value < 0.05). Conclusion: Psychoeducation using TB Cards is effective in reducing anxiety levels in tuberculosis patients in the Sikumana Community Health Center working area. Suggestion: TB Cards can be used as an alternative educational medium in Community Health Centers to support the success of TB treatment by increasing patient understanding and reducing anxiety